Asuhan Keperawatan pada NY. E dengan Diabetes Melitus Tipe II di Ruangan Muzdalifah Rumah Sakit Aisyiyah Pariaman - Salsabilla Benalivo; Ns. Mike Asmaria, S.kep, M.Ke; Ns. Hilma Yessi, S.kep, M.kep; Dr. Ns. Linda Marni, S.Pd, S.Kep, M.M.Kes (CV. ITTC INDONESIA, 2026)
According to WHO (2022), Diabetes Mellitus is one of the leading contributors to global mortality, accounting for 71% of deaths worldwide and continuing to increase. Approximately 122 million adults worldwide are living with this condition, with Type 2 Diabetes Mellitus accounting for 58.5% of all diabetes cases. In Indonesia, around 19.5 million adults were reported to have diabetes in 2021. In West Sumatra, Type II Diabetes Mellitus cases reached 245,105 cases or 13.725% in 2018. Data obtained from Aisyiyah Pariaman Hospital showed that there were 278 cases of Diabetes Mellitus in 2024, making it the fourth most common disease treated at the hospital. The purpose of this case study was to provide nursing care for a patient with Type II Diabetes Mellitus, including assessment, nursing diagnosis, intervention, implementation, evaluation, and documentation. The method used was a case study involving one patient. The research was conducted on Mrs. E in the Muzdalifah Ward of Aisyiyah Pariaman Hospital from June 9 to June 13, 2025. The results of the study identified several nursing problems, namely: unstable blood glucose levels, acute pain, impaired skin integrity, impaired physical mobility, risk of nutritional deficit, disturbed sleep pattern, and anxiety. The implementation and evaluation included monitoring blood glucose levels, wound care, administration of antibiotics, facilitation of mobility aids, provision of a high-protein diet, sleep management, anxiety reduction, and evaluation over five days. The results showed that all identified nursing problems were partially resolved. Patients are expected to maintain proper dietary habits, adhere to diabetes management diets, and adopt a healthy lifestyle to manage Type II Diabetes Mellitus effectively.